Inhibitory effects of prepulse stimuli on the electrophysiological responses to startle stimuli in the deep layers of the superior colliculus - Ding, Yu; Jiang, Huan; Xu, Na; Li, Liang (Frontiers in Neuroscience, 2024)
Prepulse inhibition (PPI) is a phenomenon where a weak prepulse stimulus inhibits the startle reflex to a subsequent stronger stimulus, which can be induced by various sensory stimulus modalities such as visual, tactile, and auditory stimuli. This study investigates the neural mechanisms underlying auditory PPI by focusing on the deep layers of the superior colliculus (deepSC) and the inferior colliculus (IC) in rats. Nineteen male Sprague-Dawley rats were implanted with electrodes in the left deepSC and the right IC, and electrophysiological recordings were conducted under anesthesia to observe the frequency following responses (FFRs) to startle stimuli with and without prepulse stimuli. Our results showed that in the deepSC, narrowband noise as a prepulse stimulus significantly inhibited the envelope component of the startle response, while the fine structure component remained unaffected. However, this inhibitory effect was not observed in the IC or when the prepulse stimulus was a gap. These findings suggest that the deepSC plays a crucial role in the neural circuitry of PPI, particularly in the modulation of the envelope component of the startle response. The differential effects of narrowband noise and gap as prepulse stimuli also indicate distinct neural pathways for sound-induced PPI and Gap-PPI.Understanding these mechanisms could provide insights into sensory processing and potential therapeutic targets for disorders involving impaired PPI, such as tinnitus.